(untitled) (Південний архів (історичні науки), 2023)
The purpose of the study is to highlight the history of breeding and the influence of the cultivation of the soft winter wheat variety Ukrainka 0246 on economic processes in Ukraine during the 20th century. The methodological basis of the study became historiographical analysis and synthesis methods and historical-systemic method used under the principles of historical objectivism. The main results of the study. The Article analyzes the history of the soft winter wheat variety Ukrainka 0246 breeding by the scientists at Myroniv breeding and research station, outlines the main methods of its reproduction and influence on the development of agriculture and the economy in Ukraine in the 20–40s of the 20th century. The Article also points out the contribution of famous scientists, in particular V. Yу. Zholtkevych, L. I. Kovalevskyi, I. M. Yeremeyev. The qualitative features of the bred wheat are characterized, in particular, its high yield – from 20 cwt/ha to 30 cwt /ha. And the sown area before 1950 reached 7 mln ha. The impact of the social and political situation in 1917–1920s on the process of organizing research and breeding activities at Myroniv station and their influence on the breeding of the variety was traced. Methods of spreading wheat are described. For instance, I.M. Yeremeyev first used ordinary peasant farms for the research and propagation of the variety. He also was the initiator of the Union of Peasants – Seed Growers in 1920. The impact of wheat yield on historical processes of the 1930s is described, attention is focused on the statistics of the harvested crop and grain procurement plans. The policy of exporting grain abroad and its impact on the situation in the country is highlighted. The emphasis is made on the process of collectivization and the role of wheat in the artificially created Holodomor of 1932–1933. The harvested crop in those years was enough to provide the population with grain, but overestimated grain procurement plans were one of the causes of the Holodomor. The conclusions summarize the significance of the soft winter wheat variety «Ukrainka 0246» on the economic policy of Ukraine. During 45 years, «Ukrainka» wheat grew in the fields not only of Ukraine, but also of other countries, and the variety itself was recognized as an international standard of strong wheat. More than 200 varieties of wheat were created on its basis.